Imajinasi Eskatologis dalam QS. Al-Qari‘ah Ayat 4–5 Perspektif Tafsir Al-Ibriz: Analisis Sosiologi Pengetahuan Karl Mannheim - Muhammad Wildan Farohi (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study aims to analyze the construction of eschatological imagination in KH. Bisri Mustofa's interpretation of Qur'an Surah Al-Qāri‘ah verses 4–5 in Tafsir Al-Ibriz and to examine its relationship with the socio-cultural context of Javanese pesantren society through Karl Mannheim's Sociology of Knowledge. This research employs a qualitative library research approach, using Tafsir Al-Ibriz as the primary source, supported by literature on Indonesian Qur'anic exegesis, Qur'anic eschatology, and Mannheim's theoretical framework. Data were analyzed descriptively and analytically by identifying eschatological symbols, examining the interpretive constructions developed by the exegete, and relating them to the socio-historical context underlying the interpretation. The findings reveal that KH. Bisri Mustofa employs local cultural symbols, such as walang (grasshopper) and wulu (feather), to concretize Qur'anic depictions of the Day of Judgment, making them more accessible to Javanese readers. From Mannheim's perspective, these symbols represent socio-religious consciousness shaped through the interaction of the Qur'anic text, pesantren intellectual tradition, and local cultural experience. The study concludes that Tafsir Al-Ibriz functions not only as a religious interpretation but also as a socially constructed body of knowledge reflecting the dynamic interaction between revelation, local culture, and social reality. These findings highlight the significance of the Sociology of Knowledge approach in enriching interdisciplinary studies of Indonesian Qur'anic exegesis.